2019
DOI: 10.1186/s12909-019-1651-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-menu and single-best-answer multiple choice questions in computer-based summative assessments: a randomised controlled trial

Abstract: Background Little is known regarding the psychometric properties of computerized long-menu formats in comparison to classic formats. We compared single-best-answer (Type A) and long-menu formats using identical question stems during the computer-based, summative, intermediate clinical-clerkship exams for nine disciplines. Methods In this randomised sequential trial, we assigned the examinees for every summative exam to either the Type A or long-menu format (four differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…The needs identification stage involves analyzing the issues with paper-based assessment that are less effective and efficient. In this phase, the school management team successfully identified these problems and studied the available school resources and assets (Bello et al, 2021;Cerutti et al, 2019;Mitra et al, 2015). In the planning phase, the school management team formulated specific objectives, identified targets and participants, and designed strategies and activities to be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…The needs identification stage involves analyzing the issues with paper-based assessment that are less effective and efficient. In this phase, the school management team successfully identified these problems and studied the available school resources and assets (Bello et al, 2021;Cerutti et al, 2019;Mitra et al, 2015). In the planning phase, the school management team formulated specific objectives, identified targets and participants, and designed strategies and activities to be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Studies at the augmentation level (n=60) employed online tests to gain better understanding of learners' current knowledge and provide additional learning opportunities. There was an emphasis on using online technologies to enable timely and often automated feedback (Herbert et al, 2019) or design tests that incorporated multimedia resources or sophisticated types of questions (Cerutti et al, 2019). These studies unanimously reported student appreciation of formative feedback from online tests (Chen & Chuang, 2012).…”
Section: Current Research Into Online Testsmentioning
confidence: 99%
“…Überraschend für uns war, dass zwar in der Evaluation die Informationsmenge, welche zur Verfügung gestellt wurde, für die Lösung als genau richtig bewertet wurde, in den Freitextkommentaren jedoch darüber hinausgehend deutlich mehr Hin-Abb. 3…”
Section: Diskussionunclassified
“…Die Erstellung der Fälle gelang hierbei mit moderatem technischem Aufwand und geringen Investitionskosten. Wünschenswert wären allerdings weitere Frageformate gewesen, beispielsweise eine Long-Menu-Option hätte die Quizabschnitte deutlich aufgewertet [ 3 ]. Da jedoch aufgrund der verpflichtend digitalen Lehre im Rahmen der Corona-Pandemie keine Zeit für eine separate Programmierung und Implementierung entsprechender Features war, musste dies für die 1.…”
Section: Diskussionunclassified